Density functionals with asymptotic-potential corrections are required for the simulation of spectroscopic properties of materials. Issue 5 (19th January 2022) - Li, Musen; Kobayashi, Rika; Amos, Roger D.; Ford, Michael J.; Reimers, Jeffrey R.
Abstract : Spectroscopic transitions in materials that involve charge transfer require asymptotically corrected density functionals. As most transitions do have some charge transfer character, use of such methods are generally warranted. Abstract : Five effects of correction of the asymptotic potential error in density functionals are identified that significantly improve calculated properties of molecular excited states involving charge-transfer character. Newly developed materials-science computational methods are used to demonstrate how these effects manifest in materials spectroscopy. Connection is made considering chlorophyll- a as a paradigm for molecular spectroscopy, 22 iconic materials as paradigms for 3D materials spectroscopy, and the VN − defect in hexagonal boron nitride as an example of the spectroscopy of defects in 2D materials pertaining to nanophotonics. Defects can equally be thought of as being "molecular" and "materials" in nature and hence bridge the relms of molecular and materials spectroscopies. It is concluded that the density functional HSE06, currently considered as the standard for accurate calculations of materials spectroscopy, should be replaced, in most instances, by the computationally similar but asymptotically corrected CAM-B3LYP functional, with some specific functionals for materials-use only providing further improvements.